Crystallization of TiO2 on sputter deposited amorphous titanium thin films - Tepe, Seda Aysel; Danisman, Murat; Cansever, Nurhan (ELSEVIER SCIENCE SA, 2022)
Titanium and titanium dioxide are both very well-known and commonly used materials in today's world. They would also be very promising materials for years to come as their more novel properties are continued to be investigated. For meeting the demands of today's technology and to fine tune its properties, titanium dioxide is still in the scope of scientists from different branches of science. In our study, sputter deposited amorphous titanium thin films on glass substrates were anodically oxidized at 0.7 V for 250, 750, 1250 s in 0.5 M H2SO4 solution to observe their crystalline structure and electrochemical properties. X ray diffraction analysis revealed rutile and anatase crystalline peaks on 250 s and 1250 s anodized samples. Additionally, electrochemical impedance spectroscopy and atomic force microscopy analysis were carried out for investigating the effect of anodization on electrochemical and surface properties of amorphous titanium thin films. Both analysis showed compressive stress related findings in oxide films due to crystallization process.
Keywords: Amorphous titanium; Thin films; Anodization; Impedance spectroscopy; ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY; ANODIC-OXIDATION PARAMETERS; CORROSION BEHAVIOR; OXIDE-FILMS; GROWTH; DIOXIDE; MECHANISMS; NANOTUBE; Materials Science